A systematic report on non-coronary cardiac CTA in 1097 patients from the German cardiac CT registry - Gitsioudis, Gitsios; Marwan, Mohamed; Schneider, Steffen; Schmermund, Axel; Korosoglou, Grigorios; Hausleiter, Jörg; Schroeder, Stephen; Rixe, Johannes; Leber, Alexander; Bruder, Oliver; Katus, Hugo; Senges, Jochen; et al. (European journal of radiology, 2020)
Purpose - To prospectively evaluate contemporary indications, safety and diagnostic impact of cardiac CTA in patients undergoing cardiac CTA examinations for non-coronary clinical indications. - Method - We analyzed 1097 consecutive patients from the German Cardiac CT Registry who underwent cardiac CTA between 2009 and 2014 due to clinically indicated non-coronary reasons using 64-slice or newer CT systems in twelve tertiary German heart centers in order to evaluate the impact of clinical indications on procedure-associated parameters. All participating centers electronically submitted patient and examination data including detailed indications, clinical symptoms, procedural parameters, complications and diagnostic results in a predefined template. - Results - The most frequent indication for non-coronary cardiac CTA was the evaluation of pulmonary vein anatomy (65.9 %, 723/1097). In the remaining cases, most frequent indications were planning before TAVI (44.5 %, 69/155), evaluation of valvular disease (31.6 %, 49/155), and evaluation of implants (5.8 %, 9/155). Non-coronary cardiac CTA required a median amount of iodinated contrast agent of 100.0mL (IQR 95.0-110.0mL). Prospectively ECG-triggered acquisition was the most frequently used protocol (74.0 %), followed by retrospectively ECG-gated acquisition with and without tube current modulation (19.9 % and 6.0 %, respectively), resulting in a mean estimated effective dose of 5.2 mSv (IQR 2.9−9.5 mSv, average conversion factor k=0.026). Overall, complication rate was very low (1.5 %). Non-coronary cardiac CTA revealed a new clinical diagnostic aspect in 3.2 % of all patients, and a new main clinical diagnosis in 2.2 %. - Conclusions - Non-coronary cardiac CTA as a routinely applied diagnostic modality is associated with a very low procedure-related rate of complications and reasonably low radiation exposure using contemporary CT systems.
Gesehen am 29.10.2020